Analisis Kemampuan Fiskus Dalam Pemeriksaan Pajak Guna Meningkatkan Kepatuhan Wajib Pajak - Tahyu, Dadang (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2011)
Regarding the importance of public awareness in achieving tax compliance, it required a competent tax administration. The competence of tax authorities are an important factor in determining taxpayer compliance, especially in the self assessment system. Lack of ability from tax authorities will have an impact on the low rate of taxpayer compliance in meeting its obligations. Therefore, in this context required a deep understanding of the tax authorities within the framework of the ability to see taxpayer compliance. Besides the ability of tax authorities, there is important factor that determine tax compliance, namely the tax audit. Tax audit is part of the tax administration that has functions to assess taxpayer compliance both formal and material. For taxpayers with low compliance rate is expected to do another inspection, to provide positive motivation for subsequent periods that goes along with the main purpose of the tax audit which is to keep the taxpayer compliance in taxation obligations. That way, the examination has a positive impact on taxpayer compliance in implementing the taxation obligation, namely to prevent the smuggling of tax by the taxpayer under investigation. Aspect capability of tax authorities, tax audits and tax compliance has a correlation to one another that are connected in a tax administration with self-assessment tax system